Pengaruh Kerja Lembur pada Produktivitas Tenaga Kerja Konstruksi - Sumarningsih, Tuti (Department of Civil Engineering, Diponegoro University, 2014)
In order to meet the construction project completion, project duration often be compressed and work accelerated, especially in case the project held behind the schedule. One of several methods to accelerated a schedule is applying overtime work. Overtime work achieves schedule acceleration by increasing the amount of hours worked by labor beyond the typical 8 hours worked per day and 40 hours worked per week. Although there may be positive short-term benefits to working an overtime schedule, the long-term consequences are typically viewed as detrimental, such as fatigue, reduced productivity and safety, and increased absenteeism. The objective of this research is to present the effects of schedule overtime on construction labor productivity, and the impact of loss labor productivity to the labor costs. Overtime in this research is defined as the hours worked beyond the normal straight time hour (08.00 – 16.00). The data were collected by field observation and interview with the foremen. Field observation held in four weeks, with 28 labors included. The result of this research show a decrease labor productivity by 8,87% - 11,84%, and increase labor costs by 58,63% - 79,31%.